(untitled) (Archives of The Medicine and Case Reports, 2024)
The establishment of successful breastfeeding is crucial for both maternal and infant health. However, many women experience challenges with milk production, leading to supplementation or early cessation of breastfeeding. Chayote (Sechium edule), a widely available and nutrient-rich vegetable, has been traditionally used to support lactation. This study aimed to investigate the effect of chayote consumption on breast milk production in postpartum women. A quasi-experimental, one-group pretest-posttest design was employed. Thirty-five postpartum women who reported concerns about milk supply were recruited. Participants consumed 600 grams of steamed chayote daily for seven days. Breast milk production was measured before and after the intervention using a standardized breast pump. Additionally, maternal perception of milk supply and infant weight gain were assessed. The mean breast milk production increased significantly from 315 ml (SD = 45) at baseline to 480 ml (SD = 55) after the intervention (p < 0.001). The majority of participants (82.9%) reported a perceived increase in milk supply. Infant weight gain also showed a positive trend, although not statistically significant. The consumption of chayote appears to be effective in enhancing breast milk production in postpartum women. This readily available and affordable dietary intervention may offer a valuable strategy to support lactation and promote breastfeeding success.